A Unique Robust Dual-Promoter-Driven and Dual-Reporter-Expressing SARS-CoV-2 Replicon: Construction and Characterization - Ying Liu; Lu Li; Khalid A. Timani; Johnny J. He (Viruses, 2022)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2, SARS2) remains a great global health threat and demands identification of more effective and SARS2-targeted antiviral drugs, even with successful development of anti-SARS2 vaccines. Viral replicons have proven to be a rapid, safe, and readily scalable platform for high-throughput screening, identification, and evaluation of antiviral drugs against positive-stranded RNA viruses. In the study, we report a unique robust HIV long terminal repeat (LTR)/T7 dual-promoter-driven and dual-reporter firefly luciferase (fLuc) and green fluorescent protein (GFP)-expressing SARS2 replicon. The genomic organization of the replicon was designed with quite a few features that were to ensure the replication fidelity of the replicon, to maximize the expression of the full-length replicon, and to offer the monitoring flexibility of the replicon replication. We showed the success of the construction of the replicon and expression of reporter genes fLuc and GFP and SARS structural N from the replicon DNA or the RNA that was in vitro transcribed from the replicon DNA. We also showed detection of the negative-stranded genomic RNA (gRNA) and subgenomic RNA (sgRNA) intermediates, a hallmark of replication of positive-stranded RNA viruses from the replicon. Lastly, we showed that expression of the reporter genes, N gene, gRNA, and sgRNA from the replicon was sensitive to inhibition by Remdesivir. Taken together, our results support use of the replicon for identification of anti-SARS2 drugs and development of new anti-SARS strategies targeted at the step of virus replication.